Comparação molecular de quatro genes relacionados à virulência nas estirpes leptospirais do sorogrupo Icterohaemorrhagiae - Correia, L.; Malliagros, L. V.; Pires, B. C.; Brasil, T.; Jaeger, L. H.; Carvalho-Costa, F. A.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Pathogenesis of leptospirosis is related to agent characteristics as well the ability to escape immune system of the host. However, the leptospires biology and virulence factors are not enough characterized and the factors for the pathogenesis and that trigger the development of the disease are still unclear.